Efficient bifacial dye-sensitized solar cells through disorder by design. Issue 5 (18th January 2016) - Miranda-Muñoz, José M.; Carretero-Palacios, Sol; Jiménez-Solano, Alberto; Li, Yuelong; Lozano, Gabriel; Míguez, Hernán
Abstract : Herein we realize an optical design that optimizes the performance of bifacial solar cells by incorporating spherical TiO2 nanoparticles of controlled size and load integrated in the working electrodes of dye-sensitized solar cells without modifying any of the usually employed components. Abstract : Herein we realize an optical design that optimizes the performance of bifacial solar cells without modifying any of the usually employed components. In order to do so, dielectric scatterers of controlled size and shape have been successfully integrated in the working electrodes of dye-sensitized solar cells (DSSCs), resulting in bifacial devices of outstanding performance. Power conversion efficiencies (PCEs) as high as 6.7% and 5.4% have been attained under front and rear illumination, respectively, which represent a 25% and a 33% PCE enhancement with respect to an 8 μm-thick standard solar cell electrode using platinum as the catalytic material. The remarkable bifacial character of our approach is demonstrated by the high rear/front efficiency ratio attained, around 80%, which is among the largest reported for this sort of device. The proposed optimized design is based on a Monte Carlo approach in which the multiple scattering of light within the cell is fully accounted for. We identified that the spherical shape of the scatterers is the key parameter controlling the angular distribution of the scattering, the most efficient devices being those in which the inclusions provide a narrow forward-oriented angular distribution of the scattered light.